Mechanical Properties of Self-Compacting Geopolymer Concrete Using Fly Ash and GGBS - S. Thirupathiraj; Renuka, S. M.; Dineshkumar, M. (Asian Journal of Engineering and Applied Technology, 2018)
Cement is the core content for the concrete mix. Manufacturing of cement causes CO2 emission which leads to the pollution, health and environmental problems like global warming to control over the adverse effect we can prefer geopolymer concrete which is not a cement concrete. Factory wastes such as fly ash, ground granulated blast furnace slag (GGBS), silica fume and Metakaolin can be used as alternate for cement. This study mainly focus on the ratio of fly ash and ground granulated blast furnace slag (GGBS) for optimum levels which nearly matches the cement concrete properties. This study involves the various tests like slump flow, compression testing, split tensile strength and flexural strength of self-compacting geopolymer concrete. Self-compacting concrete is a highly flowable concrete that spreads into the form without the need of mechanical vibration. Self-compacting concrete is a non-segregating concrete that is placed by means of its own weight. The advantages include improved constructability, Labour reduction, bond to steel, Flow into complex forms, reduced equipment wear etc. The aim of this study is to achieve an optimum self-compacting concrete geopolymer concrete mix proportion using fly ash and ground granulated blast furnace slag (GGBS). Then the study will be further extended by investigating the durability properties of self-compacting geopolymer concrete.